(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
This article is a literary review that presents a modern view on the strategy and tactics of relieving AF attacks, indications for pharmacological cardioversion (PCV) and electro-pulse therapy (EIT). Based on the presented material, international recommendations for the management of patients with AF are taken, as well as data from a number of modern studies and our own clinical experience in the treatment of arrhythmias. The article also examines the issues of emergency therapy of AF and expresses the author’s point of view on the results of a number of studies in this field of arrhythmology.